Satellite Love as a Young Adult Literature - Ayudistya, Nyiar; Wahyono, Danu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Abstract. The aims of this study is to analyze the features of young adult literature, through the intrinsic elements of a young adult literature novel. Young adult literature is a work of literature that focuses on how teenagers address the issues of adolescents. The novel Satellite Love by Genki Ferguson with 272 pages in total have several themes that considered as a young adult literature. This research used a descriptive qualitative approach to analyze the data to identify the features of young adult literature in the novel entitled Satellite Love and found what is distinguished from adult literature. In this study, some evidence was found that the characteristics of young adult literature are contained in the novel by Genki Ferguson published in 2021. It was also found that according to young adult literature, Stanton divided the plot have three stages namely, subplot, conflict, climax. Plot in a story moves quickly because it does not involve too many characters. Each chapter in Satellite Love is written from a different point of view of a teenager with a different physical appearance and a different ethnic origin. Satellite Love also deals with problems that teenagers commonly experience, such as bullying, isolation, loneliness, and falling in love and obsession. The novel Satellite Love can be concluded that most of the features of young adult literature can be represented in the novel Satellite Love.